Chinese Students, Learning Cultures and Overseas Study - Wang, Lihong. author. aut Link
X, 241 p.
Keywords: This book focuses on the phenomenon of Chinese postgraduate students studying abroad and depicts their learning trajectory as they adjust to a new culture of teaching and learning in a new environment. It uses an example from a British university to draw together intercultural learning theories to explore the impact that studying abroad has.